2015
DOI: 10.1016/j.econmod.2014.12.038
|View full text |Cite
|
Sign up to set email alerts
|

Energy management systems and market value: Is there a link?

Abstract: Abstract:This paper aims to advance in the knowledge of the economic impacts of ISO 50001 certification on firms' performance. The study hypothesizes that ISO 50001 is associated with improvements in market value of firms.We employ, on one hand, event study methodology for a sample of 40 companies listed on different stock exchanges. On the other hand, we use market reaction to the announcement of ISO 50001 as a proxy for changes in firm performance. We reveal that market reaction to the adoption of ISO 50001 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 38 publications
0
10
0
1
Order By: Relevance
“…Pham [65] and McKane et al [23] cited the challenge "Difficulty in properly evaluating the benefits generated by ISO 50001 adoption". For Pham [65], there was not sufficient foundation to affirm that the market value of the companies increases with ISO 50001 implementation.…”
Section: References Portion Of Referencesmentioning
confidence: 99%
See 1 more Smart Citation
“…Pham [65] and McKane et al [23] cited the challenge "Difficulty in properly evaluating the benefits generated by ISO 50001 adoption". For Pham [65], there was not sufficient foundation to affirm that the market value of the companies increases with ISO 50001 implementation.…”
Section: References Portion Of Referencesmentioning
confidence: 99%
“…Pham [65] and McKane et al [23] cited the challenge "Difficulty in properly evaluating the benefits generated by ISO 50001 adoption". For Pham [65], there was not sufficient foundation to affirm that the market value of the companies increases with ISO 50001 implementation. According to McKane et al [22], the complexity of measuring CO2 and energy savings due to ISO 50001 adoption is another important challenge to be faced by organizations.…”
Section: References Portion Of Referencesmentioning
confidence: 99%
“…Therefore, the assessment of certified energy management standards is considered the success of the process, according to the energy management requirements [43,44]. In the meantime, a study by Pham (2015) revealed that the adoption of ISO 50001 has quite a negative effect on the market. This result does not suggest that obtaining ISO 50001 is a bad investment [45].…”
Section: Yearmentioning
confidence: 99%
“…In the meantime, a study by Pham (2015) revealed that the adoption of ISO 50001 has quite a negative effect on the market. This result does not suggest that obtaining ISO 50001 is a bad investment [45]. To date, no guidelines can be used to measure the qualitative results of an EnMS and, thus, indicate its effectiveness and anticipated benefits in order to show the quality or sustainability levels of an organization's EnMS.…”
Section: Yearmentioning
confidence: 99%
“…Through the implementation of energy saving programs, the following benefits can be achieved [1,[5][6][7][8]:…”
Section: Introductionmentioning
confidence: 99%